2017
DOI: 10.1002/syn.21972
|View full text |Cite
|
Sign up to set email alerts
|

Pattern separation in the hippocampus through the eyes of computational modeling

Abstract: Pattern separation is a mnemonic process that has been extensively studied over the years. It entails the ability -of primarily hippocampal circuits- to distinguish between highly similar inputs, via generating different neuronal activity (output) patterns. The dentate gyrus (DG) in particular has long been hypothesized to implement pattern separation by detecting and storing similar inputs as distinct representations. The ways in which these distinct representations can be generated have been explored in a nu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
18
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
7
3

Relationship

0
10

Authors

Journals

citations
Cited by 21 publications
(18 citation statements)
references
References 125 publications
0
18
0
Order By: Relevance
“…Pattern separation is defined as the transformation of a non-simultaneous set of similar input patterns of neuronal activity into less similar output patterns [5], and is theorized to happen in the hippocampus before encoding a memory trace in order to avoid confusion between similar memories [6]. Despite a long history of research on the subject, mostly in silico [7], it is still unclear how the activity of single neurons underlies this computation.…”
Section: Introductionmentioning
confidence: 99%
“…Pattern separation is defined as the transformation of a non-simultaneous set of similar input patterns of neuronal activity into less similar output patterns [5], and is theorized to happen in the hippocampus before encoding a memory trace in order to avoid confusion between similar memories [6]. Despite a long history of research on the subject, mostly in silico [7], it is still unclear how the activity of single neurons underlies this computation.…”
Section: Introductionmentioning
confidence: 99%
“…Indeed, DG lesions impair mnemonic discrimination both in rodents (Treves et al, 2008; Kesner and Rolls, 2015; Kesner et al, 2016) and humans (Yassa et al, 2011; Baker et al, 2016; Bennett and Stark, 2016; Dillon et al, 2017). Moreover, computational models (Chavlis and Poirazi, 2017) and recent experiments (Berron et al, 2016; Knierim and Neunuebel, 2016; Madar et al, 2019a, 2019b; Woods et al, 2020) suggest that the DG circuitry supports multiple forms of pattern separation (Santoro, 2013). Whether such computations underlie mnemonic discrimination remains unclear.…”
Section: Introductionmentioning
confidence: 99%
“…Many genes affecting synaptic plasticity undergo pronounced circadian oscillations, changing the rules of synaptic plasticity depending on the time of day 6 . Theoretical and empirical work suggests that the dentate gyrus (DG) actively reduces the overlap of activity patterns coming from entorhinal cortex [7][8][9] . In vivo electrophysiology and calcium imaging experiments revealed that the majority of GCs are silent, and of the active cells, just a small fraction show spatial tuning ("place cells") [10][11][12][13][14][15][16] .…”
Section: Introductionmentioning
confidence: 99%